2021
DOI: 10.2169/internalmedicine.6434-20
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of COVID-19 Mimics in the Emergency Department

Abstract: Objective Due to the lack of specific clinical manifestations and symptoms, it is difficult to distinguish COVID-19 from mimics. A common pitfall is to rush to make a diagnosis when encountering a patient with COVID-19-like symptoms. The present study describes a series of COVID-19 mimics using an outpatient database collected from a designated COVID-19 healthcare facility in Tokyo, Japan. Methods We established an emergency room (ER) tailored specifically for patients with suspected or confirmed COVID-19 call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
3
0
1
Order By: Relevance
“…To the Editor Kurihara et al reported that 82.1% of patients with Coronavirus-2019 (COVID-19)-like symptoms were diagnosed with non-COVID-19, with potentially fatal diseases detected in 14.2% of them. In addition, they concluded that, “Several potentially fatal diseases remain masked among the wave of COVID-19 mimics” ( 1 ). We recently experienced a case of COVID-19 vaccine-related probable myocarditis that was masked at the first clinic visit.…”
mentioning
confidence: 99%
“…To the Editor Kurihara et al reported that 82.1% of patients with Coronavirus-2019 (COVID-19)-like symptoms were diagnosed with non-COVID-19, with potentially fatal diseases detected in 14.2% of them. In addition, they concluded that, “Several potentially fatal diseases remain masked among the wave of COVID-19 mimics” ( 1 ). We recently experienced a case of COVID-19 vaccine-related probable myocarditis that was masked at the first clinic visit.…”
mentioning
confidence: 99%
“…A common pitfall was to rush to make a diagnosis when encountering a patient with COVID-19-like symptoms [ 23 ]. At the opposite pole, diagnosing septic shock without assessing the overlap of other potentially fatal diseases, such as SARS-CoV-2 infection, was risky during the defined time period in which this study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Por lo que los pacientes con múltiples comorbilidades (siendo las más usuales diabetes mellitus, enfermedad renal e hipertensión) presentan una relación significativa de mayor mortalidad. [21][22][23] El aumento de la temperatura corporal y disminución de saturación de oxígeno se asoció con mayor riesgo de ingreso a la unidad de cuidados intensivos en pacientes con COVID 19. 24 Los pacientes con mayor uso de oxígeno suplementario y saturación de oxígeno presentaron una mayor asociación de mortalidad a los dos días e ingreso con un área bajo la curva de 0.65 y 0.64, respectivamente.…”
Section: Discussionunclassified